EFEKTIFITAS BUAH BIT (BETA VULGARIS) SEBAGAI DISCLOSING SOLUTION (BAHAN IDENTIFIKASI PLAK) - Diyah Fatmasari; Setiadji Musthofa; Bedjo Santoso (Odonto : Dental Journal, 2014)
Background: Bit fruit (Beta vulgaris) is plants as group of vegetables, has potencial as a source of natural dyes for food products. In dental health, a coloring agent which has contrast color with teeth is used for dental plaque identification. Disclosing solution is the most common used material for this purpose. Purpose of this study was to identify if bit fruit can substitute disclosing solution as coloring agent for plaque identification. Method: Research design was Quasi Eksperimental Research.with Posttest Only Control Group Design. Samples was 36 elementary students which divided into 2 groups. Group 1 was 18 students given disclosing solution while group 2 was given bit fruit solution. Independent t test was used to determine diferences between two groups. Result: Research results showed mean of plaque index after application of bit fruit and disclosing solution was 3,75 and 2,66 , with independent t-test resulten significancy 0,000 < 0,05. There was differences of plaque index after two group of application. Conclusion: the bit fruit was more effective to determine plaque compared to disclosing solution.